PERAN PELATIHAN, MOTIVASI DAN KOMPETENSI GURU TERHADAP KINERJA GURU PADA MADRASAH ALIYAH NEGERI (MAN) SAMPANG - Siti Nurul Hasanah; Fitra Mardiana; Chamariyah Chamariyah (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
This study aims to analyze the role of training, motivation and teacher competence on teacher performance at the State Madrasah Aliyah (MAN) Sampang. This type of research is explanatory research, the approach used is a quantitative approach with a total sample of 69 respondents. The results showed that both partially and simultaneously the training, motivation and competence of teachers partially affected the performance of teachers in the State Madrasah Aliyah (MAN) Sampang.